Perfectionism and marital satisfaction among graduate students: a multigroup invariance analysis by counseling help-seeking attitudes - Foo, Fatt Mee; Hassan, Siti Aishah; Abu Talib, Mansor; Zakaria, Noor Syamilah (Polish Academy of Sciences, Committee for Psychological Science, 2017)
This study aims to measure the latent mean difference in perfectionism and marital satisfaction by counseling help-seeking attitudes. The respondents were 327 married graduate students from a research university in Malaysia. An online self-administered questionnaire was used to collect the data. The respondents completed the Almost Perfect ScaleRevised, Dyadic Almost Perfect Scale, Marital Satisfaction Scale, and Attitudes toward Seeking Professional Psychology Help Scale. Confirmatory factor analysis was used to examined the instruments and the results indicated that construct validity were achieved. The latent mean difference in perfectionism and marital satisfaction by counseling help-seeking attitudes were tested using multigroup invariance analysis. The respondents with negative attitudes toward counseling help-seeking (n = 159) reported a higher latent mean in perfectionism but a lower latent mean in marital satisfaction compared to those with positive attitudes toward counseling help-seeking (n = 168). The implications of these findings for counseling services are discussed.